A Case of Hepatocellular Carcinoma with Haemobilia after Transcatheter Hepatic Arterial Embolization for Tumor Rupture - Kishimoto, Tomoya; Nomura, Tomohiro; Mizuno, Manatsu; Nakano, Masaya; Fukada, Akio; Taniguchi, Yoshiki; Asukai, Kei; Ohsawa, Hideki; Mokutani, Yukako; Kawada, Junji; Yoshioka, Shinichi; Fujita, Junya; et al. (Gan to kagaku ryoho, 2023)
A 79-year-old man was scheduled for surgery for hepatocellular carcinoma(HCC)after transcatheter hepatic arterial embolization for rupture. Two weeks before surgery, the patient came to our hospital with a chief complaint of back pain. First, we performed biliary drainage, under the diagnosis of HCC with obstructive jaundice due to haemobilia. Hepatectomy was performed when the patient's condition stabilized. It should be kept in mind that haemobilia may occur after TAE for HCC with bile duct tumor thrombus, and appropriate treatment should be performed when bleeding occurs.